ENGLISH TEACHERS’ STRATEGIES IN TEACHING VOCABULARY DURING COVID - 19 - Lenissa Ginting; Sintia Anastasia Situmorang (English Language Teaching Prima Journal (ELT), 2020)
Abstract This study describes the strategies used by English teachers in teaching vocabulary during the Covid-19 pandemic. The type of research used is qualitative research, where the data collection process uses observation, interview, recording and triangulation methods. The results of research conducted on two English teachers at SMA Dharma Pancasila showed that the teachers at the school taught using various strategies and varied learning methods such as telling stories in the form of narrative, question and answer, and stimulating students to learn using attractive pictures. Besides that, teachers must also continue to motivate and arouse students' enthusiasm to study more actively during the Covid-19 pandemic, and it is also hoped that teachers and parents can work together to create more effective learning conditions. Keywords: Teacher Strategies, Covid-19, Vocabulary, Online learning